Excel data analysis for dummies - Nelson, Stephen L., 1959-; Nelson, E. C. (Elizabeth C.); John Wiley & Sons (Hoboken : John Wiley & Sons, 2016)
"Put the power of Excel to work and excel at data analysis! Most businesses are drowning in data, and making sense of it all is critical. Excel is a powerful data analysis tool, and this books shows you how to use it and become a data deciphering expert. You'll learn to organize data in workbooks, create powerful magic with PivotTables and PivotCharts, and explore advanced statistical tools that take you to the next level." -- Back cover.
Part I: Getting started with data analysis -- Part II: PivotTables and PivotCharts -- Part III: Advanced tools -- Part IV: The part of tens.
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets -- Computer programs; Electronic spreadsheets -- Data processing; Data mining; Electronic books